Governance In International Paddy Industry Value Chain - Rahmat, Siti Rahyla (2019)
This study examines the requirement of the governance or regulations in paddy farming. To achieve a self-sustainable level of rice production, with the aim to ensure food security in the country, System of Rice Intensification (SRI) which is an organic cultivation method for paddy has been introduced in Malaysia. Using qualitative and field evaluation method, this study has conducted six in-depth interviews and 32 field evaluation on both organic and inorganic paddy farming. This study found that there are two leading organic agriculture regulators in the world which are IFOAM and USDA. Major difference between IFOAM and USDA is that IFOAM allows private standard setters to define their own additional criteria and set threshold levels that are above European minimum requirement. On the other hand, USDA does not allow others to set a standard that are above the federal. In Malaysia, organic farming is monitored by the Ministry of Agriculture and Agro-Based Industry Malaysia under MOS. Only 28 organic farms in Malaysia are eligible to use organic labels and are aligned with the organic production regulation by the government. This study also shows few of organic accreditation in several Asia countries including Thailand, Indonesia, Cambodia, Japan, India and China. Moreover, this study provides important understanding and a clear picture of the conventional plantation and organic plantation of paddy in Malaysia. It is important especially for the Research and Development (R&D) department to improve the quality of paddy production to meet all the requirements set up by the governance of the chain. Therefore, this research serves as a reference for Malaysian government, in achieving the objective of National Agricultural Policy to lure the bio economy in Malaysia.